Finland : 2015 Article IV Consultation-Press Release; Staff Report; Informational Annex; and Statement by the Executive Director for Finland. (IMF Staff Country Reports; Country Report ;, 2015)
This 2015 Article IV Consultation highlights that Finland's exports have suffered owing to the declines of Nokia and the paper industry, compounded by weak external demand, especially from the euro area and Russia. The current account and fiscal balances have deteriorated, with the 2014 fiscal deficit breaching the Stability and Growth Pact's 3 percent of GDP criterion. A modest recovery is projected to begin in 2015 and gradually strengthen in 2016. However, in absence of further reforms, growth is likely to remain much lower than pre-crisis. Weaker-than-expected growth in key trade partners would be a drag on exports, and spillovers from an external financial shock would create tighter financial conditions, with negative effects on output.